Biofilm Formation Is Crucial for Efficient Copper Bioleaching From Bornite Under Mesophilic Conditions: Unveiling the Lifestyle and Catalytic Role of Sulfur-Oxidizing Bacteria - Bobadilla-Fazzini, Roberto A.; Poblete-Castro, Ignacio (Frontiers in Microbiology, 2021)
Biofilm formation within the process of bioleaching of copper sulfides is a relevant aspect of iron- and sulfur-oxidizing acidophilic microorganisms as it represents their lifestyle in the actual heap/dump mining industry. Here, we used biofilm flow cell chambers to establish laminar regimes and compare them to turbulent conditions to evaluate biofilm formation and mineralogic dynamics through QEMSCAN and SEM-EDS during bioleaching of primary copper sulfide minerals at 30 ºC. We found that laminar regimes triggered the buildup of biofilm using Leptospirillum spp. and Acidithiobacillus thiooxidans (inoculation ratio 3:1) at a cell concentration of 106 cells/g mineral on bornite (Cu5FeS4) but not for chalcopyrite (CuFeS2). Conversely, biofilm did not occur on any of the tested minerals under turbulent conditions. Inoculating the bacterial community with ferric iron (Fe3+) under shaking conditions resulted in rapid copper recovery from bornite, leaching 40% of the Cu content after 10 days of cultivation. The addition of ferrous iron (Fe2+) instead promoted Cu recovery of 30% at day 48, clearly delaying the leaching process. More efficiently, the biofilm-forming laminar regime almost doubled the leached copper amount (54%) after 32 days. In-depth inspection of the microbiologic dynamics showed that bacteria developing biofilm on bornite’s surface corresponded mainly to At. thiooxidans while Leptospirillum spp. were detected in planktonic form, highlighting the role of biofilm buildup as a means for the bioleaching of primary sulfides. We finally propose a mechanism for bornite bioleaching during biofilm formation where sulfur regeneration to sulfuric acid by the sulfur-oxidizing microorganisms is crucial to prevent iron precipitation for efficient copper recovery.